The Fast Crack Growth Analysis Under Dynamic Loading with the Help of Adina - Rokach, L.V.; Neimitz, A. (Engineering Transactions, 1994)
Finite element modeling of dynamic crack growth during impact bend testing is performed using ADINA 6.1. Results are compared with the numerical data reported in literature. The influence of the time step, the Newmark method parameters, types of quadrangular finite elements and form of their mass matrix on the accuracy of dynamic stress intensity factor (DSIF) evaluation is investigated. When numerical dam ping is not used for some values of the time step, parasitic oscillations of DSIF are registered. Effective methods for elimination of these oscillations are proposed. Conditions for indirect DSIF determination using crack mouth opening displacement are investigated.